Morphological characteristics of Tenualosa ilisha (Hamilton 1822) larvae collected from Meghna river of Bangladesh - Riar, Md Golam Sajed; Ara, Roushon; Sarker, S. M. Nurul Amin Harmuj Ali; Mohd Kamarudin, Mohd Shamimy; Wahab, Md Abdul; Raushon, N. A.; Arshad, Aziz (Triveni Enterprises, 2020)
Aim : The present research was undertaken to describe the morphological development of larvae and early juveniles of hilsa shad, Tenualosa ilisha. Methodology : Samples were collected from the lower Meghna River of Bangladesh. The investigation was based on the ontogenetic development of 100 samples of T ilisha. Results : Larvae and juveniles were divided into five groups according to morphological features; yolk sac larvae (3.83 mm SL), pre flexion larvae (8.07 mm SL), flexion larvae (11.60 mm SL), post flexion larvae (14.72 mm SL) and juvenile (18.76 mm SL). The number of myomere and vertebrae ranged from 34 - 44 and 40 - 46 respectively. In the case of fin ray, the number of dorsal fin rays were 16 - 20, anal fin rays 18 - 22, pectoral fin rays 14 - 16, pelvic fin rays 7 - 9 and caudal fin rays were found to be 20 - 24, respectively, in different stages. Relationship between the mean values of the body depth and standard length differed significantly among larval and juveniles stages. Interpretation : This study mainly described the larval morphological development of hilsa, T. ilisha. The information would be beneficial for the formulation of effective sustainable management of spawning grounds of hilsa.